THE ENVIRONMENTAL PROVISIONS OF CERTAIN UEFA 4. CATEGORY FOOTBALL STADIUMS - Ráthonyi-Odor, Kinga; Ráthonyi, Gergely (Acta Carolus Robertus, 2020)
In the past almost two decades the sports sector – especially on international scales – has paid more and more attention on understanding the area of environmental protection and sustainability integrating it and also what is to be done in practice. One of the popular fields of examining the sports sector from an environmental point of view is the eco-friendly construction and operation of stadiums/arenas, as grand sports facilities have a growing significance these days giving venue to various programs apart from sport events. The purpose of this present study is to present the environmental provisions of three UEFA 4. category football stadiums. While researching the stadiums – Emirates Stadium; Signal Iduna Park, Johan Cruyff Arena (earlier Amsterdam Arena) – we particularly focused on how ecological efforts and green action can be integrated in the implementation and operation of each sports facility.
Keywords: football stadiums; sustainability; environmental protection; UEFA 4